2013
DOI: 10.1158/1055-9965.epi-13-0263
|View full text |Cite
|
Sign up to set email alerts
|

PTGS2 (Cyclooxygenase-2) Expression and Survival among Colorectal Cancer Patients: A Systematic Review

Abstract: Background: Studies have examined whether tumor expression of PTGS2 (also known as COX-2), an enzyme inhibited by nonsteroidal anti-inflammatory drugs such as aspirin, is associated with prognosis in patients with colorectal cancer. However, results to date have been mixed.Methods: Using terms for PTGS2 and colorectal cancer, the Medline, Embase, and Web of Science databases were systematically searched for studies published, in any language, until December 2011. Random effects meta-analyses were used to calcu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 54 publications
(38 reference statements)
3
59
0
Order By: Relevance
“…In CRC COX-2 was shown to be associated with a poor overall survival [48][49][50][51] and advanced CRC stage [52,53] however in another study no such correlation was found [54]. As outlined in Fig.…”
Section: Cox-2 Expression In Cancermentioning
confidence: 95%
“…In CRC COX-2 was shown to be associated with a poor overall survival [48][49][50][51] and advanced CRC stage [52,53] however in another study no such correlation was found [54]. As outlined in Fig.…”
Section: Cox-2 Expression In Cancermentioning
confidence: 95%
“…Cells were maintained in a humidified incubator at 37˚C and 5% CO 2 . Early passages (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) were used for the experiments.…”
Section: Methodsmentioning
confidence: 99%
“…There are two functional isoforms of COX: COX-1, whose expression is constitutive; and COX-2, which exhibits an inducible expression and whose products have been mainly associated with pathological processes (10). COX-1 expression has been reported to remain stable in cancer tissues, while COX-2 expression has been associated with advanced Dukes stage, poor long-term outcome and lymph node metastasis in CRC patients (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…CCND1 [17], as one member of cyclins, regulates the activity of CDK4 or CDK6 during cell cycle G1/S transition. PTGS2, also known as COX-2 [39], is involved in regulating blood vessel endothelial cell migration. VEGFA, considered to be the dominant inducer to the growth of blood vessels, could stimulate endothelial cell mitogenesis and cell migration and induce angiogenesis and vasculogenesis [26].…”
Section: Gb_accmentioning
confidence: 99%